Left-behind vs. unequal places: Interpersonal inequality, economic decline, and the rise of populism in the US and Europe - Andrés Rodríguez-Pose; Javier Terrero-Dávila; Neil Lee (Luxembourg Income Study (LIS), 2023)
Economic change over the past twenty years has rendered many individuals and territories vulnerable, leading to greater interpersonal and interterritorial inequality. This rising inequality is seen as a root cause of populism. Yet, there is no comparative evidence as to whether this discontent is the consequence of localised interpersonal inequality or stagnant growth in 'left-behind' places. This paper assesses the association between levels and changes in local GDP per capita and interpersonal inequality, and the rise of far-right populism in Europe and in the US. The analysis -conducted at small region level for Europe and county level for the US- shows that there are both similarities and differences in the factors connected to populist voting on both sides of the Atlantic. In the US, neither interpersonal inequality nor economic decline can explain populist support on their own. However, these factors gain significance when considered together with the racial composition of the area. Counties with a large share of white population where economic growth has been stagnant and where inequalities have increased supported Donald Trump. Meanwhile, counties with a similar economic trajectory but with a higher share of minorities shunned populism. In Europe, the most significant factor behind the rise of far-right populism is economic decline. This effect is particularly large in areas with a high share of immigration.
Keywords: D31; D72; R11; 330; populism; anti-system voting; interpersonal inequality; interterritorial inequality; economic growth; Europe; US